2019
DOI: 10.1093/jac/dkz397
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cefotaxime-resistant urinary Escherichia coli from primary care in South-West England 2017–18

Abstract: Objectives Third-generation cephalosporin-resistant Escherichia coli from community-acquired urinary tract infections are increasingly reported worldwide. We sought to determine and characterize the mechanisms of cefotaxime resistance employed by urinary E. coli obtained from primary care, over 12 months, in Bristol and surrounding counties in South-West England. Methods Cefalexin-resistant E. coli isolates were identified fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 38 publications
0
75
1
Order By: Relevance
“…The fourth plasmid (pIV_IncFII_DHA) was 83,429 bp in size and belonged to the IncFII plasmid family. pIV_IncFII_DHA showed high score with both the p133355_SW_C4_Cam-1 plasmid (81,724 bp) reported in 2019 in a Citrobacter amalonaticus collected from a human stool specimen in Switzerland (CP041363.1; 99.64% sequence identity, 97% sequence coverage), and with the pUB_DHA-1 plasmid (81,754 bp), present in an E. coli strain from a human urine sample in United Kingdom (MK048477; 99.55% sequence identity, 97% query coverage) (Findlay et al, 2019). The plasmid backbone carried regions responsible for replication (repA), conjugative transfer system (tra, yhfA, finO genes), maintenance (parM) and toxin-antitoxin (TA) systems (mazEF/mazEF).…”
Section: Resultsmentioning
confidence: 95%
“…The fourth plasmid (pIV_IncFII_DHA) was 83,429 bp in size and belonged to the IncFII plasmid family. pIV_IncFII_DHA showed high score with both the p133355_SW_C4_Cam-1 plasmid (81,724 bp) reported in 2019 in a Citrobacter amalonaticus collected from a human stool specimen in Switzerland (CP041363.1; 99.64% sequence identity, 97% sequence coverage), and with the pUB_DHA-1 plasmid (81,754 bp), present in an E. coli strain from a human urine sample in United Kingdom (MK048477; 99.55% sequence identity, 97% query coverage) (Findlay et al, 2019). The plasmid backbone carried regions responsible for replication (repA), conjugative transfer system (tra, yhfA, finO genes), maintenance (parM) and toxin-antitoxin (TA) systems (mazEF/mazEF).…”
Section: Resultsmentioning
confidence: 95%
“…Virotype C is considered to be the most widely distributed virotype among ST131, occurring in all ST131 clades ( 17 ). Here, virotype C was predominant among clade C1, specifically C1-M27 subclade, as also reported recently from South-West England and Europe ( 17, 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Virotype C is considered to be the most widely distributed virotype among ST131, occurring in all ST131 clades ( 17 ). Here, virotype C was predominant among clade C1, specifically C1-M27 subclade, as also reported recently from South-West England and Europe ( 17, 18 ). In contrast to several European studies which reported the virotype A as the dominated virotype among C2 clade ( 12 ), in our study virotypes E and F were found as the most common virotypes, representative of > 60% of the C2 clade strains (22 out of 34 strains).…”
Section: Discussionmentioning
confidence: 99%
“…bla CTX-M-14 was amplified from a human urinary E. coli isolated from primary care (38) by PCR with Phusion High-Fidelity DNA Polymerase (NEB, UK) using primers CTX-M-14 FW (5′-CCGGAATTCAATACTACCTTGCTTTCTGA-3′) and CTX-M-14 RV (5′-CCGGAATTCCGTAGCGGAACGTTCATCAG-3′) and ligated into pUBYT (39) at the EcoRI site. CTX-M-14 site-directed mutagenesis ( bla CTX-M-14-P170S ) was performed using the QuikChange Lightning Site-Directed Mutagenesis Kit (Agilent, USA) with the primer CTX-M-14-P170S-FW (5′-TCTGGATCGCACTGAATCTACGCTGAATACCGC-3′).…”
Section: Methodsmentioning
confidence: 99%